An Economic Analysis of Major Determinants of Expenditures on Public Education - McMahon, Walter W. (The Review of Economics and Statistics, 1970)
T HIS paper considers the major influences on the level of current expenditures on public primary and secondary education. Its purpose is to clarify their interrelation, directing attention toward those determinants that can be shown to be of major importance overall in both cross section and time series data. There are a number of empirical studies of determinants of public primary and secondary education in the literature. Among the most recent and thorough are those by Hirsch [14], Shapiro [29], Miner [23], Burkhead [7], James [18, 19] and Pryor [26] . There is, however, the lack of a structural theory in all of these studies, and this lack of a sufficiently explicit theoretical framework somewhat limits the capacity to interpret the economic meaning of the statistical results.1 A neat separation of economic and noneconomic factors is hardly possible. But it is possible to distinguish the economic framework of the problem which interrelates influences on the demand for public education, costs of producing it, and tax behavior (via tax handles or other revenue sources). It is also possible to bring to bear on the analysis of resources for education some of the developments in the broader context of public expenditure theory (e.g., Musgrave [25] and others) and the recent developments in consumption theory (e.g., Ando-Modigliani [1], Houthakker [16], and others).2 Although this is not a normative study of efficient allocation (for which see Bowles [4] for example), it can make use of certain advantages offered by education as a case study in public expenditure theory. For most school administrative units are single purpose units making quasi-independent expenditure decisions. Importance also derives from the fact that education is an extremely large industry, engaged in the furthering'of growth through human capital formation, and in the reduction of inequality. Part I considers the demand, production cost, and tax behavior structural equations. Attention is then turned to their joint solution and the reduced form public expenditure functions that are the result. The reduced forms maintain the degree of comparability to other studies that we desire for the large ones have used single equatioii methods (e.g., Miner [23], James [18, 19]) with data for a sample of individual districts. Others have focused on the relation of the aggregate expenditure-income ratio to per capita income (e.g., Musgrave [25], Pryor [26 pp. 182-226].) Part II considers empirical estimates of these reduced forms for cross-section data among states for 1955-1956, the mid-point of the postwar period, and for time series data for 1946-1968.